Penggunaan Metode Diskusi Diawali Dengan Pemberian Pertanyaan dan Pemberian Tugas Dengan Memperhatikan Kemampuan Siswa Dalam Menyelesaikan Masalah Fisika - Handhika, Jeffry; Purwandari, Purwandari (Jurnal Pendidikan, 2009)
The research is served to identify : (1) the significance of discussion method started by giving the question and the assignment, (2) the difference between higher and lower level of student ability in solving problem of Physics , (3) the interaction of using discussion method started by giving questions and assignments, and student ability in problem solving of Physics, to Physic learning achievement in Thermodynamics.This Research was conducted from May 2008 to June 2008, using experiment method. The population is all students of grade XI SMA Negeri Mojogedang Karanganyar. The sample is assigned to two out of all classes, those are: IPA I as Experiment I class and IPA II as experiment II class. The data were collected using test, documentation and observation. The data was analyzed under two ways anova constructively served by Minitab 15 software.The data analysis results in conclusions that: (1) there is a significant difference of using discussion method started by giving questions and assignments, (2) there is a difference between higher and lower level student ability in problem solving of Physics, (3) there is interaction of using discussion method started by giving the question and the assignment, student ability in problem solving of Physics to learning achievement in Physics. Following Anova test results in conclsion that discussion method started by giving the assignments is tentatively more effective than that started by giving the questions. The high student ability in problem solving of Physics also gives the better influence.Key wordsÂ :Â Discussion Method, Problem solving of Physics